(untitled) (Harmoni, 2018)
Tourism has been a trend in the modern life of human in order to, among other purposes, be a medium to search healing. This could be caused by the assumption that modern treatment of healing for many people is expensive, therefore people look for cheap and affordable alternatives. A number of studies in tourism are still limited in social, economic, and cultural aspects. This research scrutinises the spirituality in the theological perspective of the people, especially the theological base of the healing searchers. Applying a fieldwork research, it is discovered that while soaking at the Banyu Panas, they spiritually expect to gain healing from any diseases. This is believed as prayer fulfilment, universality, and connectedness. The research discovers that the cultural tourism for spiritual therapy is still unified with other visitors of recreational objectives. In the future, there is a need to develop special space for therapy and be separated from other visitors of recreational objectives, hence it will create comfort and privacy. This way may expectedly enhance the visits of people to the touristic destination.